International trade in educational services in the conditions of digital transformation - A. M. Kanunnikova (Вестник университета)
The article analyzes the methodological foundations of international trade in educational services and current trends in the development of the global education market. It was revealed that one of the key areas of development is the digitalization of the global education market. Digital academic mobility has been gaining popularity in recent years, especially in the conditions created by the Covid-19 pandemic. At the end of 2019 – beginning 2020, the education sector was shocked due to a sharp transition to the online format: neither teachers, nor students, nor schoolchildren in most countries of the world were ready for this. At present it can be concluded that the world has experienced the pandemic and people have adapted to the digital educational environment, but in many regions there is no Internet connection and not everyone has access to a computer, therefore there is a digital divide. According to the United Nations Sustainable Development Goals, by 2030 it is planned to provide all the inhabitants of the planet with quality education throughout their lives. In recent years a large number of EdTech companies have emerged competing for a leading position in the global online education market. Distance learning platforms allow people from all over the world to receive training in areas of interest to them. But in the era of digital transformation the issue of the problems and prospects for the development of the online education market is relevant.